Kinetics of anaerobic elemental sulfur oxidation by ferric iron in Acidithiobacillus ferrooxidans and protein identification by comparative 2-DE-MS/MS - Kucera, Jiri; Bouchal, Pavel; Cerna, Hana; Potesil, David; Janiczek, Oldrich; Zdrahal, Zbynek; Mandl, Martin (Antonie van Leeuwenhoek, 2012)
Elemental sulfur oxidation by ferric iron in Acidithiobacillus ferrooxidans was investigated. The apparent Michaelis constant for ferric iron was 18.6 mM. An absence of anaerobic ferric iron reduction ability was observed in bacteria maintained on elemental sulfur for an extended period of time. Upon transition from ferrous iron to elemental sulfur medium, the cells exhibited similar kinetic characteristics of ferric iron reduction under anaerobic conditions to those of cells that were originally maintained on ferrous iron. Nevertheless, a total loss of anaerobic ferric iron reduction ability after the sixth passage in elemental sulfur medium was demonstrated. The first proteomic screening of total cell lysates of anaerobically incubated bacteria resulted in the detection of 1599 protein spots in the master two-dimensional electrophoresis gel. A set of 59 more abundant and 49 less abundant protein spots that changed their protein abundances in an anaerobiosis-dependent manner was identified and compared to iron- and sulfur-grown cells, respectively. Proteomic analysis detected a significant increase in abundance under anoxic conditions of electron transporters, such as rusticyanin and cytochrome c(552), involved in the ferrous iron oxidation pathway. Therefore we suggest the incorporation of rus-operon encoded proteins in the anaerobic respiration pathway. Two sulfur metabolism proteins were identified, pyridine nucleotide-disulfide oxidoreductase and sulfide-quinone reductase. The important transcription regulator, ferric uptake regulation protein, was anaerobically more abundant. The anaerobic expression of several proteins involved in cell envelope formation indicated a gradual adaptation to elemental sulfur oxidation.
Keywords: kinetika; anaerobióza; proteomika; Ferrous Compounds; Sulfur; fyziologická adaptace; Acidithiobacillus; síra; Electrophoresis, Gel, Two-Dimensional; Oxidation-Reduction; Ferric Compounds; Anaerobiosis; Bacterial Proteins; Proteomics; železité sloučeniny; Tandem Mass Spectrometry; 2D gelová elektroforéza; Kinetics; oxidace-redukce; tandemová hmotnostní spektrometrie; železnaté sloučeniny; bakteriální proteiny; Adaptation, Physiological